Screening for developmental delay in the setting of a community pediatric clinic: a prospective assessment of parent-report questionnaires - Rydz, David; Srour, Myriam; Oskoui, Maryam; Marget, Nancy; Shiller, Mitchell; Birnbaum, Rena; Majnemer, Annette; Shevell, Michael I (Pediatrics (Evanston), 2006)
Our goal for this study was to prospectively test whether parent-completed questionnaires can be effectively used in the setting of a busy ambulatory pediatric clinic to accurately screen for developmental impairments. Specific objectives included (1) assessing the feasibility of using parent-report instruments in the setting of a community pediatric clinic, (2) evaluating the accuracy of 2 available screening tests (the Ages and Stages Questionnaire and Child Development Inventory), and (3) ascertaining if the pediatrician's clinical judgment could be used as a potential modifier. Subjects were recruited from the patient population of a community clinic providing primary ambulatory pediatric care. Subjects without previous developmental delay or concerns noted were contacted at the time of their routine 18-month-old visit. Those subjects who agreed to participate were randomly assigned to 1 of 2 groups and completed either the Ages and Stages Questionnaire or Child Development Inventory. The child's pediatrician also completed a brief questionnaire regarding his or her opinion of the child's development. Those children for whom concerns were identified by either questionnaire underwent additional detailed testing by the Battelle Development Inventory, the "gold standard" for the purposes of this study. An equal number of children scoring within the norms of the screening measures also underwent testing with the Battelle Development Inventory. Of the 356 parents contacted, 317 parents (90%) agreed to participate. Most parents correctly completed the Ages and Stages Questionnaire (81%) and the Child Development Inventory (75%). Predictive values were calculated for the Ages and Stages Questionnaire and the Child Development Inventory (sensitivity: 0.67 and 0.50; specificity: 0.39 and 0.86; positive predictive value: 34% and 50%; negative predictive value: 71% and 86%, respectively). Incorporating the physician's opinion regarding the developmental status of the child did not improve the accuracy of the screening questionnaires. Three important conclusions were reached: (1) parent-completed questionnaires can be feasibly used in the setting of a pediatric clinic; (2) the pediatrician's opinion had little effect in ameliorating the accuracy of either questionnaire; and (3) single-point accuracy of these screening instruments in a community setting did not meet the requisite standard for development screening tests as set by current recommendations. This study raises important questions about how developmental screening can be performed, and we recommend additional research to elucidate a successful screening procedure.